State-of-the-Art Management of Complications of Myeloma and Its Treatment. (7th April 2010) - Hartley-Brown, Monique A.; Sullivan, Daniel M.; Baz, Rachid
Abstract : Multiple myeloma is an incurable disease, although patient survival has increased with the availability of novel agents. Both multiple myeloma and its therapies often affect the renal, immune, skeletal, hematologic, and nervous systems. The resulting organ dysfunctions often impair the quality of life of affected patients, complicate and limit subsequent therapies, and may result in significant mortality. Research on the treatment of complications of multiple myeloma has been limited; hence, preventative and management strategies for patients with these complications are heterogeneous and often based on anecdotal experience. In this paper, we review the effects of myeloma and the novel therapies on organ systems and suggest management strategies.